Resistência e performance na arte de João Cota - Câmara, Arandi Robson Martins (2008)
Researching about the art of tell and the tales told by João Cota is somehow revisiting the oral tradition and social practice in the story-telling art. It takes into consideration the resistance this art still exerts, mainly by using the performance of oral transmission and receptiveness to tales. The study of this practice contributes to the vivacious and dynamcis permanence of this authentic and traditional storyteller of his repertory and of his form to tellin our culture. Story-telling is part of the humankind living heritage communicated by means of popular wisdom. Despite the risk of vanishing into thin air, along with their narrators, the tales still manage to resist the contemporary mass culture model. How long further will stories like the ones narrated by João Cota be able to resist to strong and stronger structures dictated by writing and other communication means? João Cota s practice in story-telling will be studied not only as a proposal to identify the presence of this practice and the oral cultural resistance but also, through the performance prospective, to identify the oral transmission and receptiveness to the tales that are part of this storyteller s repertoire. In other words: what he tells, how he tells it, and why he tells it. The advent of new technologies such as internet, through which people can easily communicate with others in different parts of the world, and the greater and greater expansion in the writing skill concept interfere the maintenance of the oral tradition elements present in João Cota s narratives and inserted in the Brazilian culture. This has become more visible in the latest decades although we still notice the living tradition and permanence of the story-telling practice in several parts of the country through their wise storytellers. Our research target will require - in each of its study stages reference to works by several theoreticians namely Paul Zumthor, Mikhail Bakhtin, Câmara Cascudo, theoreticians from the receptiveness aesthetic, from the written culture history, from oral cultures and reading practices, from tradition and the Brazilian Culture of oral story-telling. In order to get to know and draw a profile of this storyteller, we ve chosen to use the comprehensive interview method by French Sociologist Jean Claude Kaufmann. The originality in the method consists of the qualitative data put together in situ , concentrated on the storyteller s narratives/speeches recorded on tape, which will be the focal point of this study. Our analysis method is based on tireless sessions of listening to interviews out of which we gathered information related to the storyteller, his practice in telling the tales, and his repertoire